Hyper IgE (Job's) Syndrome: A Primary Immune Deficiency with Oral Manifestations - Esmaeilzadeh , Mohammad; Soleymani , Ali Asghar; Mozafar, Sedigheh; Tariverdi, Navid; Fatemi , Seyed Ali; Khosrozamiri, Mahta (Journal of Dental School, 2024)
Hyper-immunoglobulin E syndrome (HIES), also known as Job's syndrome, is a rare primary immunodeficiency disorder characterized by a classic triad: elevated immunoglobulin E (IgE) levels, recurrent pneumonia with pneumatocele formation, and recurrent cold skin abscesses. Case A 5-year-old girl was referred to the pediatric dentistry department for tooth decay and multiple dental abscesses. Her medical history revealed elevated serum IgE levels, and she was receiving treatment with warfarin due to a history of jugular vein thrombosis. Clinical examination showed numerous skin abscesses alongside multiple eczemas. Angular cheilitis, de-papillation of the tongue, deep furrows on the tongue, numerous intraoral ulcerated lesions, poor oral hygiene, and gingivitis were seen in the intraoral examination.Due to the systemic conditions and the child's non-cooperation, treatment under general anesthesia was planned. Conclusion Dentists play an essential role in the early diagnosis of HIES and in monitoring their oral health conditions. Timely extraction of over-retained primary teeth can reduce the necessity for complex treatments, thereby facilitating the management of patients with Job's syndrome.